Perbedaan Tingkat Pengetahuan, Sikap, dan Perilaku mengenai Pencegahan Covid-19 pada Mahasiswa Medis dan Non-Medis di Universitas Syiah Kuala - Cut Gina Inggriyani; Teuku Romi Imansyah Putra; Khoirul Nadya Aprilia Sagala (Universitas Muhammadiyah Semarang, 2022)
Background: Coronavirus Disease 2019 (COVID-19) is an infectious disease caused by infection with the new coronavirus, namely the Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2) virus and has been designated a global pandemic by WHO. Health prevention and promotion efforts have been continuously carried out and developed to reduce the spread of COVID-19, but the knowledge, attitudes, and practices of community has not been evaluated. Objective: The purpose of this study was to evaluate the knowledge, attitudes and behavior regarding the prevention of COVID-19 between medical and non-medical students at Syiah Kuala University. Methods: This study used an observational analytic design with a cross sectional approach using primary data. The sample of this study was 12 medical students and 98 non-medical students from all faculties at Syiah Kuala University, the sample selection used a proportional random sampling technique. Data were collected by filling out an online questionnaire (g-form) which had been tested for validity by the researcher. Data analysis used univariate analysis and bivariate analysis using the Mann-Whitney test with a significance level of p = 0.05. Results: The statistical test showed a significant difference in the level of knowledge, attitude, and behavior between medical and non-medical students (with p value 0.05). Conclusion: there are differences in the level of knowledge, attitudes, and behavior regarding the prevention of COVID-19 among medical and non-medical students at Syiah Kuala University.